Area Selective Polymer Brush Deposition. Issue 16 (3rd July 2017) - Cummins, Cian; Shaw, Matthew T.; Morris, Michael A.
Abstract : Polymer brush films with chemical functionality to attach to site‐specific substrate areas are introduced for area‐selective deposition (ASD) application. The results presented detail a novel methodology and open a new exciting process for ASD practices that can facilitate the precise deposition of dense metal, semiconductor, or dielectric films. Abstract : Polymer brush films with chemical functionality to attach to site specific substrate areas are introduced for area selective deposition (ASD) application. It is demonstrated that polymer brushes with chemically defined end sites can be selectively bound to copper‐specific regions of patterned copper/silica (Cu/SiO2 ) substrates. The process described overcomes various limitations of currently used technology including cost, complexity, and throughput, with potential implications for future electronic devices and nanomanufacturing. A comparative study of amine‐terminated polystyrene and amine‐terminated poly‐2‐vinyl pyridine polymer brushes (i.e., PS‐NH2 and P2VP‐NH2 ) with similar molecular weights display contrasting behavior on patterned Cu/SiO2 line features. Further, a thiol terminated poly‐2‐vinyl pyridine polymer brush (i.e., P2VP‐SH) is investigated as a direct spin‐on process to fabricate a metal oxide layer atop Cu areas only. The results presented here detail a novel methodology and open a new exciting process for ASD practices that can facilitate the precise deposition of dense metal, semiconductor, or dielectric films. We also discuss the applicability of polymer brushes to ASD uses going forward.